2018
DOI: 10.1103/physrevlett.121.235003
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of Positrons Exceeding 1 s in a Supported Magnetic Dipole Trap

Abstract: An ensemble of low-energy positrons injected into a supported magnetic dipole trap can remain trapped for more than a second. Trapping experiments with and without a positive magnet bias yield confinement times up to τ A = (1.5±0.1) s and τ B = (0.28±0.04) s, respectively. Supported by single-particle simulations, we conclude that the dominant mechanism limiting the confinement in this trap is scattering off of neutrals, which can lead to both radial transport and parallel losses onto the magnet surface. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…On the way towards creating a magnetically confined laboratory pair-plasma we have achieved various milestones such as 100% [4] injection efficiency and long (>1 s) [5] confinement of positrons. Measurements with the newly added electron gun indicate that electrons can be injected successfully even while the applied settings are optimized for positron injection.…”
Section: Discussionmentioning
confidence: 99%
“…On the way towards creating a magnetically confined laboratory pair-plasma we have achieved various milestones such as 100% [4] injection efficiency and long (>1 s) [5] confinement of positrons. Measurements with the newly added electron gun indicate that electrons can be injected successfully even while the applied settings are optimized for positron injection.…”
Section: Discussionmentioning
confidence: 99%
“…Confinement times exceeding 1 s were observed, and this was determined to be limited by diffusion associated with elastic collisions with residual gas neutrals (Horn-Stanja et al. 2018). Longer confinement is, therefore, expected in future experiments operated at lower base neutral pressure.…”
Section: Magnetic Confinement Of Low-density Pair Plasmasmentioning
confidence: 99%
“…The main result is best summed up with a quote from Helander's paper (Helander 2014):'in summary, it has been found that the electrostatic instabilities causing turbulence and transport in magnetically confined electron-ion plasmas are largely absent in low-density electron-positron plasmas'. This work has been subsequently extended by analytic as well as computational methods, to include electromagnetic effects (Helander & Connor 2016), geometric effects associated with a magnetic dipole geometry (Mishchenko, Plunk & Helander 2018a;Kennedy et al 2020), tokamak and stellarator configurations (Kennedy et al 2018;Horn-Stanja et al 2019), contamination of a positron-electron plasma by ions (Mishchenko et al 2018b) and non-neutrality of the positron-electron plasma (Kennedy & Mishchenko 2019). In certain magnetic geometries (including the dipole and the stellarator) and in certain parameter regimes, one can even show that nonlinear stability prevails (Helander 2017).…”
Section: Ramifications For Plasma Turbulence: the Universal Instabilimentioning
confidence: 99%
“…In particular, periodic orbits in the equatorial plane have been explored extensively 7 , and there are also a few branches of periodic orbits in the Meridian plane at relatively high energies with distinct orbital shapes [3][4][5] . At low energies, due to the presence of approximate adiabatic invariant, the problem can be further simplified 13,14 , and the results, the so-called guiding center approximation, have been applied to studies of pulsars, radiation belts, and dynamics of particles in magnetic confinement devices 12,15,16 .…”
Section: Introductionmentioning
confidence: 99%